Pengaruh Riwayat Berat Badan Lebih Dan Tempat Tinggal Terhadap Status Gizi - Rachmawati, Yulia; Sriyanti, Sriyanti (Poltekkes Kemenkes Jambi, 2024)
Background : Adolescents are a group that is vulnerable to nutritional problems. Overnourished adolescents are at risk of becoming overnourished in adulthood and are a risk factor for degenerative diseases with high morbidity and mortality. Methods: This study used a cross-sectional design to analyze the effect of history of overweight and residence on nutritional status at SMAIT Peradaban Al Izzah Sorong City. The study was conducted from March to July 2022 with a sample of 76 students. The sampling technique used pursposive sampling. The statistical analysis used was chi-square Results: The results of statistical tests in this study showed that there was an effect of history of overweight (p=0.032) and residence (p-0.043) on nutritional status. Conclusion : The conclusion of this study is that there is an influence of history of overweight and residence on nutritional status. Keywords : Overweight, Residence, Nutritional Status, Adolescents